The Externality Of Global Covid-19 And Policy Response On Macroeconomic Stability In Indonesia: Back To Basic - Farida Farida; Nur Wahyuni; Marhalinda Marhalinda; Nursina Nursina; Estu Mahanani (Universitas Muhammadiyah Prof. DR HAMKA., 2022)
The COVID-19 pandemic has had an externality impact on the world's economy, including Indonesia's. Considering Indonesia has an open system economy, International economic turmoils, along with the COVID-19 and Indonesia's weak external stability, have cast a dreary outlook of a future crisis. Therefore, capacity-based policies are necessary to encourage economic recovery and avoid a contraction. The applied model is an open-economy simple equation from the aggregate aspects of supply and demand. The research result shows that external financing does not lead to investment spillover in Indonesia. The policy response in this research suggests the need for an expansive fiscal policy that creates jobs. The expected policy implications are to ease the reliance on foreign fundings for development and prioritize support for domestic industries. In alleviating the COVID-19 effect in the short-term, the right policy is to maintain consumption through cash social assistance, but the distribution must be closely monitored.